Pola Komunikasi Hubungan Jarak Jauh Keluarga Merantau Dalam Membentuk Karakter Remaja: Studi Kasus di Desa Pakelan Kelurahan Kasihan Kabupaten Wonogiri) - Wahyuni, Mira; Wangi, Maya Sekar; Sihabuddin, Sihabuddin (Solidaritas, 2024)
ABSTRACTIn forming a child's character, the role of parents is needed. Children's growth and development really depends on the communication patterns taught by parents to children. Complex problems regarding the characteristics of adolescents are an important role for parents considering that parents are the people who educate, accompany, communicate, supervise, direct and are also the main teachers for children. Therefore, researchers are interested in conducting research on long- distance communication patterns in shaping children's character in Pakelan Village, Kasihan District. This research aims to analyze how communication patterns between parents and children shape the character of teenagers. To analyze this communication pattern, researchers used communication pattern theory. This type of research is descriptive qualitative research by conducting interviews with 18 informants who are residents of the Pakelan Village community. From the results of this research it can be concluded that the communication patterns carried out by parents and teenagers as well as the role of family companions through circle and star communication can work effectively. In forming the character of teenagers, parents and companions can communicate well even though there are inhibiting factors from parents who are far away and parents' time is limited.Keywords: Communication Patterns, Long Distance Relationships, Adolescent Characters